PERANAN FORUM KERUKUNAN UMAT BERAGAMA (FKUB): STUDI KASUS PELAKSANAAN PBM NO.9 DAN NO.8 TAHUN 2006 DI JAKARTA UTARA - Asnawati Asnawati (Research and Development Center for Guidance for Religious Societies and Religious Services, the Research and Development and Education and Training Agency of the Ministry of Religious Affairs of the Republic of Indonesia (MORA), 2012)
The Government has issued a Joint Ministerial Regulation (PBM) Minister of Religious Affairs and Minister of Home Affairs No. 9 and 8 Year 2006 on Guidelines for the Implementation of Regional Head of Maintenance Tasks for Religious Harmony, Empowerment Forum for Religious Harmony and the Construction of Houses of Worship on March 21, 2006. The FKUB was born among the people, by the community and to society. The birth had been preceded by the agency FKUB FKKUB which is used as a tool for communication, acknowledgement, aspiration, and contribution towards the community. FKUB can also be a forum for social action together and build together a lasting social relationship. North Jakarta FKUB formation is facilitated by the government as the implementation of the publication of PBM in 2006 which preceded smoothly at the end of 2007 the number of board 17.